Social Interaction of the Visually Disabled Through Facebook Social Media at the Iss Reflexology Clinic Kebon Jeruk West Jakarta - Sakaril, Gufroni Sakaril (Jurnal Visi Komunikasi, 2025)
Social media has brought many changes in communication and community interaction. This condition also occurs in the disabled community, especially the blind. This study aims to determine the social interaction through Facebook social media from blind people with disabilities at ISS Reflexology Kebon Jeruk, West Jakarta. According to Gillin and Gillin, there are two types of social processes that arise as a result of social interaction, namely associative and disassociative. This study uses a qualitative descriptive method. Blind people use Facebook social media to increase their friends, self-expression, existence and entertainment. Facebook media also allows them to work together to provide the information they need. Most of them give positive comments so that associative interactions occur. While there are also negative comments that cause disassociative interactions.